Pembiayaan Bermasalah pada BPRS Bhakti Sumekar Cabang Madya Jember : Strategi Penanganan dan Penyelesaiannya - Fardela, Yusfi Nila; Sari, Maheni Ika; Setianingsih, Wahyu Eko (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study was to determine the strategy of handling and resolving problem financing at BPRS Bhakti Sumekar Madya Jember Branch. This research is qualitative research with a descriptive approach. A sample of 22 respondents was obtained using purposive sampling technique. Data was obtained using interviews, observation, documentation, and questionnaires and analyzed using SWOT Analysis. The results showed the results of the SWOT analysis of BPRS Bhakti Sumekar Madya Jember Branch that a growth-oriented strategy is used to implement the strategy, this is because the IE matrix shows that the highest overall score is in quadrant I. Where BPRS Bhakti Sumekar in this quadrant is in a very favorable position. BPRS Bhakti Sumekar has many capabilities and strengths that can be optimized to overcome threats and weaknesses in BPRS Bhakti Sumekar Madya Jember Branch. Keywords: BPRS Bhakti Sumekar Madya Jember Branch, Handling Strategy, Settlement Of Problem Financing.